Seroprevalence of Transfusion Transmitted Infections among Blood Donors at Referral Neuroscience Hospital in Bangladesh (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: Transfusion transmitted infections (TTI) have become the main concern regarding the safe use of blood in clinical practice in Bangladesh.Objective: To assess the status of transfusion transmitted infections among the apparently healthy blood donors in Bangladesh.Methodology: This retrospective study was carried out among 15,478 blood donors from November 2022 to October 2023 in Department of Transfusion Medicine, at National Institute of Neurosciences and Hospital (NINS&H), Dhaka, Bangladesh. All the samples were screened for Hepatitis B Virus (HBV), Hepatitis C Virus (HCV), Human Immunodeficiency Virus (HIV), Syphilis and Malaria to see the prevalence of TTI.Results: Among 15,478 donors, 167 (1.079 %) were positive for TTIs. Seropositivity of HBV, HCV, HIV, and syphilis were 0.795%, 0.032%, 0.006% and 0.246% respectively. No blood donor was tested positive for malarial parasite. Conclusion: Hepatitis B Virus infection is the most common Transfusion transmitted infection in Bangladesh, followed by Syphilis. Journal of National Institute of Neurosciences Bangladesh, January 2025;11(1):9-12